'In the night kitchen': A scoping review on the night eating syndrome. (February 2022) - Muscatello, Maria Rosaria Anna; Torre, Giovanna; Celebre, Laura; Dell'Osso, Bernardo; Mento, Carmela; Zoccali, Rocco Antonio; Bruno, Antonio
Background: First described in 1955, night eating syndrome refers to an abnormal eating behavior clinically defined by the presence of evening hyperphagia (>25% of daily caloric intake) and/or nocturnal awaking with food ingestion occurring ⩾ 2 times per week. Aims: Although the syndrome is frequently comorbid with obesity, metabolic and psychiatric disorders, its etiopathogenesis, diagnosis, assessment and treatment still remain not fully understood. Methods: This review was conducted according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines; PubMed database was searched until 31 October 2020, using the key terms: 'Night Eating Syndrome' AND 'complications' OR 'diagnosis' OR 'drug therapy' OR 'epidemiology' OR 'etiology' OR 'physiology' OR 'physiopathology' OR 'psychology' OR 'therapy'. Results: From a total of 239 citations, 120 studies assessing night eating syndrome met the inclusion criteria to be included in the review. Conclusion: The inclusion of night eating syndrome into the Diagnostic and Statistical Manual of Mental Disorders -5 'Other Specified Feeding or Eating Disorders' category should drive the attention of clinician and researchers toward this syndrome that is still defined by evolving diagnostic criteria. The correct identification and assessment of NES could facilitate the detection and the diagnosis of this disorder, whose bio-psycho-social roots support its multifactorial nature. The significant rates of comorbid illnesses associated with NES and the overlapping symptoms with other eating disorders require a focused clinical attention. Treatment options for night eating syndrome include both pharmacological (selective serotonin reuptake inhibitors, topiramate and melatonergic drugs) and non-pharmachological approaches; the combination of such strategies within a multidisciplinary approach should be addressed in future, well-sized and long-term studies.